Goat Milk Casein Peptides as Potential α-Amylase Inhibitors: A Computational and Experimental Approach - Sumlang, Gavriel Hagai Paulus; Handoyo, Rumaisha Lale; Laksitorini, Marlyn Dian; Astuti, Endang; Raharjo, Tri Joko (Indonesian Journal of Chemistry, 2025)
Goat’s milk proteins can undergo hydrolysis during digestion, producing peptides that may inhibit α-amylase and help treat type 2 diabetes with minimal side effects. Identifying the amino acid composition of these peptides is essential for determining their inhibitory potential. Recent in silico digestion methods have been developed to generate specific peptides. This study aims to identify α-amylase inhibitory peptides from goat’s milk casein hydrolyzate using in silico digestion, followed by peptide synthesis and activity assay. Peptides were derived from goat’s milk casein hydrolyzed using in silico digestion. Molecular docking was employed to predict protein-peptide interactions utilizing the HADDOCK2.4 server, CABS-dock, and PepSite 2 server. Peptides EDVPSER and TNAIPYVR could inhibit α-amylase with IC50 values of 14.16 ± 0.65 and 76.58 ± 2.13 µM, respectively. In vitro evaluation confirmed that EDVPSER from αS1-casein exhibited α-amylase inhibitory potential. This peptide could be developed as a potential therapeutic agent for type 2 diabetes, offering a natural and targeted approach to α-amylase inhibition. Peptide EDVPSER may serve as a basis for further research and development of antidiabetic treatments derived from goat’s milk proteins.